Acute kidney injury aggravated by treatment initiation with apixaban: Another twist of anticoagulant-related nephropathy - Sergey V. Brodsky; Nilesh S. Mhaskar; Sampath Thiruveedi; Rajnish Dhingra; Sharon C. Reuben; Edward Calomeni; Iouri Ivanov; Anjali Satoskar; Jessica Hemminger; Gyongyi Nadasdy; Lee Hebert; Brad Rovin; et al. (The Korean Society of Nephrology, 2017)
Anticoagulant-related nephropathy (ARN) was initially described in patients on warfarin (as warfarin-related nephropathy) and recently in those using dabigatran. Herein, we report clinical history and kidney biopsy findings in a patient on apixaban (Eliquis). Initiation of treatment with apixaban resulted in aggravation of preexisting mild acute kidney injury (AKI). A few days after apixaban therapy, the patient became oligoanuric, and kidney biopsy showed severe acute tubular necrosis with numerous occlusive red blood cell casts. Only one out of 68 glomeruli with open capillary loops had small segmental cellular crescent. Therefore, there was major discrepancy between the degree of glomerular injury and the glomerular hematuria. Considering that the onset of this AKI was associated with apixaban treatment initiation, we propose that this patient had ARN associated with factor Xa inhibitor (apixaban), which has not previously been described. Monitoring of kidney function is recommended after initiation of anticoagulant therapy.